2021
DOI: 10.1111/bph.15652
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing the anthelmintic praziquantel to treat psoriasis

Abstract: Background and Purpose The anthelmintic drug praziquantel has been used as a standard treatment for schistosomiasis for over 40 years. This study aimed to repurpose praziquantel to treat psoriasis. Experimental Approach Psoriasis‐like skin inflammation was induced in mice (C57 and Balb/C) by topical application of imiquimod or intradermal injection of recombinant IL‐23. Praziquantel was either orally or topically administered during the psoriasis induction period. Key Results Mice treated with either oral or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…C57BL/6 mice are commonly used and well-known animal models for skin studies. 14,18,19 And the use of UVB light to induce experimental photoaging in mice is a widely accepted method due to its ability to mimic the effects of chronic UV exposure in humans. 20,21 The maximum dose of UVB radiation applied in our study was 300 mJ cm −2 , which is approximately equivalent to the UVB dose received during 15 minutes of sun exposure in Beijing in May, as computed using the solar calculator developed by Diffey.…”
Section: Discussionmentioning
confidence: 99%
“…C57BL/6 mice are commonly used and well-known animal models for skin studies. 14,18,19 And the use of UVB light to induce experimental photoaging in mice is a widely accepted method due to its ability to mimic the effects of chronic UV exposure in humans. 20,21 The maximum dose of UVB radiation applied in our study was 300 mJ cm −2 , which is approximately equivalent to the UVB dose received during 15 minutes of sun exposure in Beijing in May, as computed using the solar calculator developed by Diffey.…”
Section: Discussionmentioning
confidence: 99%
“…We have found no previous study that evaluated the anti-proliferative activity of ZLE and praziquantel in Schistosoma-mansoni-induced liver proliferation. However, Hao et al demonstrated that praziquantel has an antiproliferative effect during the treatment of psoriasis in mice by inhibiting STAT3 phosphorylation, thereby suppressing Th17 immunity [45]. In addition, many studies highlight the anti-proliferative potential of ZLE in cancer patients.…”
Section: Discussionmentioning
confidence: 99%